2015
DOI: 10.4269/ajtmh.14-0620
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Modeling of Malaria Endemicity Using Serological Indicators of Exposure Collected Through School Surveys

Abstract: Ethiopia has a diverse ecology and geography resulting in spatial and temporal variation in malaria transmission. Evidence-based strategies are thus needed to monitor transmission intensity and target interventions. A purposive selection of dried blood spots collected during cross-sectional school-based surveys in Oromia Regional State, Ethiopia, were tested for presence of antibodies against Plasmodium falciparum and P. vivax antigens. Spatially explicit binomial models of seroprevalence were created for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…This may provide a useful means to identify villages that are less responsive for any given reason to current interventions and may require more specific interventions, such as vector control, increased resources for coverage, or twice-a-year MDA. Seroprevalence is increasingly being used to generate models for estimation of transmission dynamics in near-elimination contexts, most notably in malaria [ 43 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may provide a useful means to identify villages that are less responsive for any given reason to current interventions and may require more specific interventions, such as vector control, increased resources for coverage, or twice-a-year MDA. Seroprevalence is increasingly being used to generate models for estimation of transmission dynamics in near-elimination contexts, most notably in malaria [ 43 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the spatial random effects, the model range remained relatively constant across models, although quite a bit smaller compared to other spatial analyses of malaria prevalence in sub-Saharan Africa. Ashton and colleagues used spatial modelling with a Bayesian framework to assess the spatial variation of malaria ( Plasmodium falciparum and Plasmodium vivax ) among 5914 school children in Oromia Regional State, Ethiopia [ 51 ]. They described range as the distance at which similarities in climatic factors and ecology would be expected, and found that it was approximately 45 km in the P. falciparum model [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ashton and colleagues used spatial modelling with a Bayesian framework to assess the spatial variation of malaria ( Plasmodium falciparum and Plasmodium vivax ) among 5914 school children in Oromia Regional State, Ethiopia [ 51 ]. They described range as the distance at which similarities in climatic factors and ecology would be expected, and found that it was approximately 45 km in the P. falciparum model [ 51 ]. Although the outcome assessed by Ashton and colleagues was similar to that of the Ghana trial ( P. falciparum parasitaemia), the range from each study may have been less comparable due to differences in key study characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling could also be used to assess the level of hidden/unidentifiable cases/infections that would hinder (or would not hinder) elimination (e.g., asymptomatic or individuals with minor symptomology who would not seek treatment). As transmission declines, the addition of serological measures of past exposure [ 65 , 98 – 102 ] or active community-based transmission measurements and reactive case management [ 103 107 ] may be considered. Modelling can estimate the incremental benefit of adding specific surveillance activities to an already established surveillance system and could examine cost-effectiveness issues [ 48 , 108 ], specific epidemiologic aspects of contract tracing [ 109 ], and the target product profile of diagnostics [ 25 , 65 , 66 ] in case-investigation or foci-investigation settings.…”
Section: Opportunitiesmentioning
confidence: 99%